Analisis Kasus Tindak Pidana Pencurian Uang ATM oleh Petugas Pengisi Uang di Kota Batam Menggunakan Routine Activity Theory (RAT) - Mohd. Kharris Maulana; M. Khasali Hakim (Mahkamah : Jurnal Riset Ilmu Hukum, 2025)
The research entitled Analysis of ATM Money Theft Crimes by ATM Cashiers in Batam City Using Routine Activity Theory (RAT) focuses on describing the elements of theft crimes, the threat of theft crimes, and cases of ATM money theft by ATM cashiers in Batam City. The research method used a normative legal research method with a case approach and a conceptual approach. The results of this study are as follows: The crime of theft is a crime against property as regulated in Chapter XXII of Book II of the Criminal Code, specifically Article 362, which contains subjective and objective elements. The types include ordinary theft, aggravated theft, and petty theft. The occurrence of theft is influenced by internal factors, such as the perpetrator's intention, and external factors, such as circumstances that support the crime. In the case of theft by ATM cash replenishment officers, the crime was committed through abuse of work access (special access crime). Based on Routine Activity Theory (RAT), crime occurs due to three main elements, namely a motivated perpetrator, a suitable target, and a lack of adequate supervision.